Islamic Value-Based Student Management for Islamic Character Development: A Qualitative Case Study at Junior High School - Lilis Suryani; Hakmi Wahyudi (Universitas Islam Negeri Palopo, 2026)
Despite the growing body of literature on student management in Islamic schools, most existing studies remain descriptive and have not systematically examined how modern management functions can be integrated with Islamic values to foster students’ Islamic character. This study aims to explore the concept and implementation of Islamic value-based student management in shaping the Islamic character of students at SMP IT Syahruddiniyah Kampar Kiri. The study employs a qualitative approach using a case study design. Participants included the school principal, the vice principal for student affairs, six subject teachers, three dormitory supervisors, and eight students, selected purposively based on their involvement in student management practices. Data were collected through in-depth interviews, structured observations, and documentation, and analyzed using the Miles and Huberman interactive model through data condensation, data presentation, and drawing conclusions. The results reveal that student management is carried out through the POAC functions (Planning, Organizing, Executing, and Controlling) integrated with Islamic values. Notably, the actuating (implementation) function—particularly through habit-forming programs such as congregational prayer, Quran memorization, and Islamic extracurricular activities—proved most significant in shaping students’ disciplined, religious, and responsible character. Theoretically, this study reveals that classical management theory (POAC) alone cannot fully explain the process of internalizing spiritual values; therefore, it needs to be integrated with Lickona’s character education theory and Al-Ghazali’s Islamic ethics concepts. Practically, Islamic schools are encouraged to institutionalize character-based organizing and holistic supervision systems, and to develop structured character training programs for educators as a prerequisite for effective Islamic value-based student management.